Retinopathy of Prematurity and Neonatal Risk Factors: A Prospective Cohort Study (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Retinopathy of Prematurity (ROP) is a disease process mostly reported in preterm and Low Birth Weight (LBW) neonates. Early detection of ROP in these groups and identification of associated neonatal factors and their prevention can prevent wide range of visual morbidity from impairment of vision to blindness in later life. The aim of this study was to determine prevalence of ROP and to identify neonatal risk factors for the development of ROP in preterm and LBW infants. Materials and methods: A total of 105 LBW infants weighing